2022
DOI: 10.3329/sja.v20i2.63583
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer demand-supply gap and avenues for policy revisits in Nepal

Abstract: Nepal's farmers report fertilizer shortages yearly, especially for rice, wheat, and maize production. A reliable and established approach to estimating the actual demand for fertilizers for different crops and cropping seasons is lacking. Therefore, it is difficult to project the types and quantity of fertilizer to import and allocate across various regions in the country. With the direct involvement of the Government of Nepal (GoN) in fertilizer import, price (subsidy), and distribution, together with the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A major challenge in the three systems, with the highest score of 4.41 among all 33 indicators, is the timely unavailability of an adequate quantity of fertilizers from the socio-economic and market category. In 2021, the technical demand for major fertilizers - Urea, Diammonium Phosphate (DAP) and Muriate of Potash (MOP) - was 1.29 million metric tonnes, with 40 % (0.6 milliom metric tonnes) of it considered as effective demand at the national level [ 30 , 64 ]. Generally, imports from the neighbouring countries met fertilizer demands in Nepal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major challenge in the three systems, with the highest score of 4.41 among all 33 indicators, is the timely unavailability of an adequate quantity of fertilizers from the socio-economic and market category. In 2021, the technical demand for major fertilizers - Urea, Diammonium Phosphate (DAP) and Muriate of Potash (MOP) - was 1.29 million metric tonnes, with 40 % (0.6 milliom metric tonnes) of it considered as effective demand at the national level [ 30 , 64 ]. Generally, imports from the neighbouring countries met fertilizer demands in Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…This is exactly the period before the survey was conducted. As indicated by Gautam et al [ 64 ], the existing fertilizer supply meets only 60 % of the effective demand with an even greater gap in western Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…Following FDD 2020, of the over 600 agrovet dealers registered across provinces as of April 2022, more than half (approximately 315) had already sold subsidized fertilizer to farmers in 2021 (Gautam, Gaihre et al., 2022). Whether or not the directive promoted equitable and efficient distribution by agrovets is assessed in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…However, the national average fertilizer application is 87 kilograms (kg) per hectare, which is lower than the South Asian (SA) average of 135 kg per hectare (WDI, 2018). The current supply of subsidized fertilizer in Nepal is only about 60% of estimated annual demand of 840,000 metric tons (t) (Gautam, Gaihre et al, 2022). Kyle et al (2017) reported that only 25% of farmers could purchase all the fertilizer they sought.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation